2012
DOI: 10.1111/j.1365-2524.2012.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Advance Directives as a complex and multistage intervention: a realist systematic review

Abstract: Psychiatric Advance Directives (PADs) are documents that allow users with severe and chronic mental illnesses to notify their treatment preferences for future crisis relapses and to appoint a surrogate decision‐maker for a period of incompetence. Despite many supposed clinical and organisational benefits, their take‐up rate has remained very low and their clinical evaluation has given contradictory results for organisational outcomes. Intermediary results are available, however, which rely on different theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 66 publications
1
70
1
1
Order By: Relevance
“…The study followed the conclusions of the literature review mentioned above (Nicaise et al 2013) and was in two phases, which were carried out in Belgium between 2010 and 2011.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study followed the conclusions of the literature review mentioned above (Nicaise et al 2013) and was in two phases, which were carried out in Belgium between 2010 and 2011.…”
Section: Methodsmentioning
confidence: 99%
“…At the intervention design stage, the literature review reported that the range of stakeholders involved in the drawing up of PADs was one key variable among types of PADs (Henderson et al 2008;Nicaise et al 2013). When developed with a view to enhancing user autonomy, PADs were meant to be produced by the user alone or within a facilitation process, but without the involvement of clinicians (Amering et al 2005;Atkinson et al 2004;Khazaal et al 2008;Sherman 1998;Swanson et al 2006b;Van Citters et al 2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research suggests very high consumer interest in PADs, but studies have found low rates of actual completion (2)(3)(4). PADs are challenging to complete without assistance, and there are misunderstandings of processes involved, concerns that directives may not be followed, and feelings of uncertainty about directing future decisions in unknown circumstances.…”
Section: Resultsmentioning
confidence: 99%